Performance of the Michigan drying simulation model with a new drying rate concept - DOI: 10.4025/actasciagron.v31i4.3872 - Dalpasquale, Valdecir Antoninho; Sperandio, Décio; Kolling, Evandro Marcos (Acta Scientiarum. Agronomy, 2009)
New formulation of the Michigan State University – MSU drying simulation model is proposed, based on Page’s thin-layer equation. It was derived, and the new drying rate formulation was used to define the humidity ratio of the air, and to complete the definition of the product temperature. All these resulted in less derivatives approximated by finite differences. The improved MSU model led to precise results, with large flexibility in time and space increments when simulation is made through finite differences, arriving to the solutions in less time, due to less derivatives numerically approximated.